Short-Term Outcomes after Combined Colon and Liver Resection for Synchronous Colon Cancer Liver Metastases: A Population Study - Abbott, Andrea M.; Parsons, Helen M.; Tuttle, Todd M.; Jensen, Eric H. (Annals of surgical oncology, 2013)
Introduction The timing of surgical resection for stage IV colon cancer with liver metastasis and the safety of simultaneous colon and liver resection remains controversial. The purpose of our study was to evaluate short-term outcomes after combined colon and liver resection (CCLR) versus colon resection (CR) or liver resection alone (LR) using a population database. Methods The National Inpatient Sample was used to select patients who had surgery for colon cancer from 2002 to 2006. We evaluated for in-hospital morbidity, mortality, and prolonged length of stay (PLOS). Our analysis was done using design-weighted unadjusted analysis and logistic regression. Results We identified 361,096 patients during our study period (CCLR 3,625; CR 322,286; LR 35,185). CCLR was not associated with an increased risk of complications (odds ratio (OR) 1.12; 95 % confidence interval (CI) 0.94–1.33; P = 0.21) or PLOS (OR 1.19; 95 % CI 0.99–1.4; P = 0.06) compared with CR. In-hospital mortality occurred in 3.5 % of patients who underwent CCLR and was not significantly associated with mortality compared with CR alone (OR 1.17; 95 % CI 0.79–1.74; P = 0.43). Liver lobectomy with CR was associated with a PLOS and a trend toward increased morbidity and mortality. Significant predictors of complications, mortality, and PLOS included: age >70 years, male gender, nonprivate health insurance, and Elixhauser score >1. Conclusions CCLR with limited liver resection can be performed with similar morbidity and mortality to colectomy alone. For patients who require hepatic lobectomy, however, strong consideration should be given to a staged approach.